Students’ Oral Presentation Problems and Teacher`S Role in their Solutions - Kurbonova Oysha Beknazarovna (Researchparks Publishing, 2022)
The present article deals with the importance of oral presentation of learners and its challenges, as well as teacher’s role in their solutions.